Peran Ilmu Kalam dalam Memperkuat Spiritualitas Umat Islam - Hairani, Esi; Putri, Elisa Miranda (LP2M Universitas Islam Ahmad Dahlan, 2024)
The spirituality of Muslims is decreasing due to ignorance regarding the meaning of religion. This decline in the spirituality of Muslims can be marked by the large number of Muslims who are not totally religious, such as many Muslims who still abandon their obligatory worship, then do not follow Islamic law correctly, so a way is needed to can increase the spirituality of Muslims. Kalam science, as an important branch of Islamic theology, has a significant role in enhancing the spirituality of Muslims. This study aims to examine how the main concepts in kalam science, such as tawhid (the oneness of Allah), the attributes of Allah, and understanding qada and qadar, can strengthen faith and spiritual awareness. Through literature analysis and philosophical approaches, it was found that kalam science not only functions as a means to defend beliefs from various intellectual challenges and skepticism, but also as a tool to deepen individuals' understanding of their relationship with God. The results of the research show that mastering the science of kalam can help Muslims develop inner calm, firmness of faith, and deeper spiritual appreciation, which ultimately contributes to the formation of a more devout and pious person.